2016
DOI: 10.18203/2320-1770.ijrcog20164353
|View full text |Cite
|
Sign up to set email alerts
|

A 3 year retrospective study on gestational trophoblastic disease in a government obstetrical tertiary care centre

Abstract: Background: The aim of this study is to assess the post diagnostic outcome of Gestational Trophoblastic Disease, a heterogeneous group of disorders, in a government obstetrical tertiary care centre. Methods: The study was conducted in the Institute of Obstetrics & Gynecology, Madras Medical College as a retrospective study. A total of 75 cases were studied over a 3 year period from January 2012 to December 2015. The parameters which were studied included age group, antecedent pregnancy, beta hCG values, histop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Right salpingectomy was performed and a histopathological examination of the fallopian tube revealed choriocarcinoma in both cases. This was similar to the study conducted by Veeraraghavan G et al 2 In their study, the patient presented with suspicion of ruptured ectopic pregnancy, however, histopathological examination failed to reveal molar tissue. Post-operatively, after 1 month, the patient had rising beta-hCG levels so single-agent chemotherapy was started.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Right salpingectomy was performed and a histopathological examination of the fallopian tube revealed choriocarcinoma in both cases. This was similar to the study conducted by Veeraraghavan G et al 2 In their study, the patient presented with suspicion of ruptured ectopic pregnancy, however, histopathological examination failed to reveal molar tissue. Post-operatively, after 1 month, the patient had rising beta-hCG levels so single-agent chemotherapy was started.…”
Section: Discussionsupporting
confidence: 90%
“…10 The mean age of presentation in this study was 25.4 years which was in concordance with other studies by Jagtap SV et al and Veeraraghavan G et alwith 24.5, and 23.5 years respectively. 2,5 However, a study conducted by Koirala A et al showed a mean age of 22 years. 8 Early age of marriage may be related to early occurrence of GTD in this region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, all cases of ectopic pregnancy (14) and spontaneous abortion (06) which were included in posttreatment monitoring of β-hCG value shown reduced serum level. Amongst 8 cases of MGCT, 1 patient died in follow-up, and all 5 cases who shown elevated β-hCG were monitored post-treatment for prognostic purpose and effectiveness of therapy or surgery.…”
Section: Discussionmentioning
confidence: 96%